Methylenenedioxymethamphetamine (MDMA Ecstasy) suppresses the innate immune system : a critical role for the anti-inflammatory cytokine interleukin-10 - Boyle, Noreen (Trinity College (Dublin, Ireland). Department of Physiology, 2007)
3,4-methylenedioxymethamphetamine (MDMA; “Ecstasy”) is a ring-substituted phenylisopropylamine and globally abused drug that has been implicated to have immunosuppressive effects in animals and humans. Here MDMA was shown to suppress production of the pro-inflammatory and Th1 promoting cytokine IFN-γ in response to an in vivo lipopolysaccharide (LPS) challenge in mice. Impaired IFN-γ production was accompanied by reduced expression of IL-12 and IL-15; two cytokines involved in IFN-γ induction. MDMA also resulted in impaired IFN-γ signalling, indicated by reduced STAT1 phosphorylation and reduced expression of several IFN-γ inducible molecules, namely the chemokine interferon inducible protein 10 (IP-10), the co-stimulatory molecule CD40, and the enzyme responsible for nitric oxide synthesis, INOS. Furthermore, MDMA down-regulated cell surface expression of MHC class II and the co-stimulatory molecules CD40, ICAM-1 (CD54) and B7.2 (CD86) on dendritic cells and macrophages; these molecules are required for effective antigen presentation, and T-cell activation. Consistent with its ability to interfere with antigen presentation, MDMA suppressed T-cell activation in the mixed lymphocyte reaction (MLR) signifying that the proliferative capacity of stimulator cells was abolished. In addition, MDMA suppressed antigen-specific cytokine responses to the protein antigen KLH.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin